Judeophobia and the New Testament: texts and contexts - Rollens, Sarah E.; Vanden Eykel, Eric M.; Warren, Meredith J. C. (William B. Eerdmans Publishing Company, 2025)
"The spirit and voice of ancient ethnic bigotry (esp. anti-Semitism) rears its head time and again in the New Testament; the editors and contributors seek to explain, contextualize, engage, problematize, and offer pedagogical strategies for dealing with these difficult texts"--